2008
DOI: 10.1111/j.1365-2958.2008.06391.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of specific TraD–TraM recognition during F plasmid‐mediated bacterial conjugation

Abstract: SummaryF plasmid-mediated bacterial conjugation requires interactions between a relaxosome component, TraM, and the coupling protein TraD, a hexameric ring ATPase that forms the cytoplasmic face of the conjugative pore. Here we present the crystal structure of the C-terminal tail of TraD bound to the TraM tetramerization domain, the first structural evidence of relaxosome-coupling protein interactions. The structure reveals the TraD C-terminal peptide bound to each of four symmetry-related grooves on the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
95
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(98 citation statements)
references
References 47 publications
3
95
0
Order By: Relevance
“…An X-ray structure of the TraD C-terminal tail bound to TraM shows that the TraD tail forms extensive contacts with the TraM monomer and, furthermore, that as many as four TraD C-terminal tails can bind a single TraM tetramer. These findings imply that a TraD hexamer establishes extensive contacts with TraM in vivo, thus forming the basis of a highly specific relaxosome-T4CP interaction (181). In this system, the T4CP carries the unstructured C-terminal tail responsible for F plasmid recognition and binding.…”
Section: Substrate Receptor Activitymentioning
confidence: 93%
“…An X-ray structure of the TraD C-terminal tail bound to TraM shows that the TraD tail forms extensive contacts with the TraM monomer and, furthermore, that as many as four TraD C-terminal tails can bind a single TraM tetramer. These findings imply that a TraD hexamer establishes extensive contacts with TraM in vivo, thus forming the basis of a highly specific relaxosome-T4CP interaction (181). In this system, the T4CP carries the unstructured C-terminal tail responsible for F plasmid recognition and binding.…”
Section: Substrate Receptor Activitymentioning
confidence: 93%
“…In the E. coli F plasmid transfer system, the TraD F receptor recruits the F plasmid in part through binding of the relaxosome subunit TraM. An X-ray structure of the TraD-TraM interaction revealed specific contacts between TraD F 's C-terminal acidic residues and TraM (20,92). Genetic studies confirmed that the TraD F -TraM F interaction promotes efficient F plasmid transfer and also that this interaction strongly inhibits transfer of the MOBQ plasmid RSF1010 through the F T4SS (20,93).…”
Section: Discussionmentioning
confidence: 99%
“…The F plasmid-encoded TraD T4CP and many T4CPs associated with effector translocator systems possess a fourth, C-terminal domain (CTD) of variable lengths and sequence compositions. Studies of TraD's CTD established its critical role in recruitment of the F plasmid to the F-encoded T4SS (20), but the contributions of CTDs to effector protein trafficking have not been evaluated (2).…”
mentioning
confidence: 99%
“…The VirB4 tree showed a more scattered distribution of relaxase families, especially among MPF T plasmids. From a functional point of view, although T4CPs interact with components of both the relaxosome and the T4SS, the T4CP-relaxosome interactions seem to be more system specific (94,96,97,101). Besides, T4CP-encoding genes are usually adjacent to the genes coding for the relaxosome components (50,57), with gene order conservation being another sign of coevolution and functional relatedness.…”
Section: Coevolution Of Mobilization and Conjugationmentioning
confidence: 99%